Evaluating the association between blood types and COVID-19 infection: A retrospective investigation carried out in the Northern Emirates of United Arab Emirates - Manjunatha Goud, Manal Mahmoud Sami Mohammed Abdelghani, Laxminarayana Kurady Bairy, Ashika Anu John, Jenibel Leela Rex Pancras Prabu, Anisha Sridhar, Tarig Hakim Merghani Hakim, Sathvik Belagodu Sridhar, Javedh Shareef (Journal of Applied Pharmaceutical Science, 2025)
The coronavirus 2019 (COVID-19) disease pandemic has profoundly affected health care, other societal systems, and the global economy. To explore possible associations with infection risk and clinical outcomes, this retrospective cross-sectional study examined the distribution of ABO and Rh blood types among 217 COVID-19 survivors (184 students and 33 faculty members) from RAK Medical and Health Sciences University in the United Arab Emirates. Data on blood group, post-COVID complications, medical history, smoking and alcohol use, vaccination history, and demographics were gathered. IBM SPSS Statistics for Windows, version 29. 4.5.1. (IBM Corp., Armonk, NY), was then used to analyze the data statistically. The study discovered substantial links between blood type, Rh factors, and COVID-19 severity. Compared to other blood groups (A, B, and AB), which had fewer symptoms, those with blood type O were more vulnerable and had more severe symptoms. An increased vulnerability to COVID-19 has also been associated with the presence of the Rh antigen. Understanding these correlations is essential to enhancing risk evaluations and treatment plans, which may improve patient outcomes. Further extensive studies with bigger sample numbers are required to validate these results and investigate underlying processes.
Keywords: ABO blood group system, COVID-19, WHO (SARS-CoV-2), retrospective studies, United Arab Emirates